Once again on the meaning of philosophy - Čepulis, Nerijus (Religija ir kultūra, 2008)
Traditional Western philosophy as upholding of the Greek wisdom at the same time is also a striving to being, totality, and completeness. Such thinking and its total attempt to be, that often becomes violence, nowadays is receiving more and more incredulity and criticism. The phenomenological thinker of Jewish descent E. Levinas radically resists totality as a continuous attempt at a universal synthesis in a whole history of philosophy. The Greek thinking always attempted to reduce any experience, everything, that has significance, into a complete system, and without leaving anything outside itself to become an absolute thinking. Levinas looks for an alternative. The concept of totality and any systematization in his alternative thinking are ruptured by the concept of Infinity that enables us to think otherwise and outside of being. Before looking at the world from the perspective of being it is necessary to question the being itself by starting from the other than being. The other than being, or the Good, is prior to being and gives it significance.